(untitled) (Literary Voice, 2025)
Jeff Goldberg is an Actor and Film Director who, after finishing his Bachelors in Film and Television from Boston University, moved to Paris to attain Graduate degree in Film direction from EICAR, The International Film School of Paris, and embarked upon his professional career. While in his early 20’s, Jeff wrote and directed his first independent feature film on the streets of Paris that was selected to the St. Petersburg International Film Festival. On the heels of that success, he began working as a director and screenwriter with French, American and Indian producers winning several prestigious screenwriting awards. After moving to India in his 30’s, he directed a string of short films that were selected at several international film festivals and has staged hundreds of theatres shows all over India. In conjunction with his film work he has also been writing, directing and acting for the stage producing over 20 productions at some of India’s most renowned venues and festivals. As an educator Jeff has taught at some of the leading film schools and acting programmes in the world; The Lee Strasberg Institute (NYC), EICAR, The International Film School of Paris, The School of Visual Arts (NYC) and Fordham University (NYC). Currently, Jeff runs one of the finest acting studios in India, The Jeff Goldberg Studio and has worked with many of India’s top talents and a variety of NGOs; Salaam Bombay (educational initiative for slum children), Teach for India and Being with Beti (women’s rights). Jeff’s shows have played to sold-out audiences all over India. His work cuts across genres ranging from drama to comedy, classics to experimental. He dares to challenge the conventions of theatre with each new production, making sure to incorporate his school of acting The Goldberg Method. He regularly tackles classics and original work pushing the boundaries each time he stages a show. Jeff happens to be one of the most popular trainers for acting workshops in Mumbai. He is extremely vocal about all the issues that he brings out via literary stories and performances and he loves meeting the youth with the sense of responsibility to be handed over to them. That is the responsibility of taking care of this world with the art of acting, the art of connecting people and the art of performing for humanity. Dr. Bhagyashree Varma, Associate Professor of English at Mumbai University interviewed Jeff Goldberg to unravel the mystique about the active experimentalist and thinker artist in Theatre and film industry.